Serum factors, cell membrane CD14, and beta2 integrins are not required for activation of bovine macrophages by lipopolysaccharide. - Jungi, T W (1997)
The role of serum factors such as lipopolysaccharide (LPS)-binding protein (LBP) and of macrophage-expressed CD14 and beta2 integrins in the activation of bovine macrophages by LPS was investigated. Macrophage activation was determined by measuring tumor necrosis factor production, NO generation, and upregulation of procoagulant activity by LPS (Escherichia coli O55:B5) at concentrations of 100 pg/ml to 100 ng/ml. The 50% effective dose for LPS was 1 order of magnitude higher than that for activating human macrophages. Macrophages were activated by LPS in the presence of serum or in the presence of albumin demonstrated to be free of LBP. The capacity to react to LPS in the absence of LBP was not due to the acquisition of LBP during a previous culture in serum. It was then established which CD14-specific antibodies block LPS binding to monocytes. Among the CD14-specific antibodies recognizing bovine mononuclear phagocytes (60bca, 3C10, My4, CAM36, VPM65, CMRF31, and TUK4), the first four blocked the binding of LPS-fluorescein isothiocyanate to bovine monocytes at low concentrations. Anti-CD14 antibodies did not block LPS-mediated activation of bovine bone marrow-derived macrophages, monocyte-derived macrophages, and alveolar macrophages. This was observed in experiments in which anti-CD14 concentrations exceeded the 50% inhibitory dose by >30-fold (3C10 and My4) or >300-fold (60bca), as defined in the binding assay described above. Monocyte-derived macrophages from an animal deficient in beta2 integrins and control macrophages were activated by similar concentrations of LPS, suggesting that beta2 integrins are not important bovine LPS receptors. Thus, in bovine macrophages, LPS recognition pathways which are independent of exogenous LBP, of membrane-expressed CD14, and of beta2 integrins may exist.